MONETARY OBLIGATION IN CASHLESS SETTLEMENT IN BANKS - Gaponenko, Vladimir; Klochikhin, Vjacheslav; Grishmanovskii, Denis; Rusanov, Michail; Gridneva, Olga (Revista Inclusiones, 2020)
In this article, we study the legal essence of monetary obligation and its role in cashless settlements in the banking system. We describe the features of monetary obligations in the banking payment systems and the obligatory and legal nature of cashless and electronic holdings. We also characterize the relationship between cash, cashless, and electronic money and study the role of the contract of the banking account.